Assessing Mozambique's exposure to coastal climate hazards and erosion - Cabral, Pedro (2019)
Cabral, P., Augusto, G., Akande, A., Costa, A., Amade, N., Niquisse, S., ... Santha, R. (2017). Assessing Mozambique's exposure to coastal climate hazards and erosion. International Journal of Disaster Risk Reduction, 23, 45-52. https://doi.org/10.1016/j.ijdrr.2017.04.002